Gut microbiota dysbiosis in diabetic nephropathy: mechanisms and therapeutic targeting via the gut-kidney axis - Jiang, Haiyan; Wang, Xiaoran; Zhou, Wei; Huang, Zhili; Zhang, Wen (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD) is the primary microvascular complication of diabetes and a leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD) worldwide, with its prevalence on the rise. Recent evidence has highlighted the crucial involvement of gut microbiota (GM) dysbiosis in the pathogenesis and progression of DKD, mediated through the gut-kidney axis. At the core of this process is a dynamic network involving metabolic, immune, and barrier dysfunction. Renal impairment—such as that seen in uremia—disrupts gut microbial composition and metabolic function. In turn, dysbiosis compromises intestinal barrier integrity, resulting in increased exposure to endotoxins and a reduction in the production of beneficial metabolites, notably short-chain fatty acids (SCFAs). This triad manifests as: (1) impaired metabolism, marked by decreased SCFAs (e.g., acetate), which weaken anti-inflammatory and immunomodulatory effects, alongside an accumulation of uremic toxins like trimethylamine N-oxide (TMAO) that trigger inflammatory pathways and renal fibrosis; (2) immune dysregulation, where increased endotoxin translocation (e.g., lipopolysaccharide, LPS) provokes systemic inflammation, oxidative stress, and immune cell infiltration (such as macrophages), contributing to renal inflammatory and fibrotic responses; and (3) barrier dysfunction, in which compromised intestinal barrier accelerates the translocation of detrimental microbial components, perpetuating a vicious cycle that exacerbates glomerulosclerosis, tubular injury, and renal function decline.Collectively, metabolic, immune, and barrier alterations reinforce one another and drive DKD progression via gut-derived metabolites and immune activation. Targeted interventions aiming to modulate the GM—using probiotics, prebiotics, or synbiotics—show promise in improving metabolic profiles, restoring gut barrier function, and mitigating DKD phenotypes. This review systematically elucidates the metabolism–immunity–barrier mechanisms by which GM dysbiosis contributes to DKD and discusses the translational potential of microbiome-targeted therapies. Further studies are needed to validate these findings and assess their long-term clinical efficacy.